2011
DOI: 10.1016/j.fcr.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of trait-specific germplasm and developing a mini core collection for efficient use of foxtail millet genetic resources in crop improvement

Abstract: Foxtail millet is an important staple crop in some parts of China, India and Japan, and a potential bioenergy source. The grains are rich source of protein, fiber, minerals and vitamins. We had earlier reported the development of a core collection (155 accessions) of foxtail millet. This study was initiated to identify trait-specific germplasm for agronomic and nutritional traits, and to develop a mini core through multilocational evaluation of the foxtail millet core collection. One hundred and fifty-five acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…Earlier studies have reported protein content of 9.2 to 11.2% using a few germplasm (Kulkarni and Naik, 2000;Kewat et al, 2016). Average Zn (23-25 mg kg −1 ) and protein (7.9-8.5%) contents in the kodo millet accessions used in this study were greater than those in finger millet germplasm (Zn 19.9 mg kg −1 , protein 7.3%) (Upadhyaya et al, 2011a), and Ca content (190-213 mg kg −1 ) was greater than in foxtail millet (146 mg kg −1 ) (Upadhyaya et al, 2011b) and proso millet (165 mg kg −1 ) (Vetriventhan Table 7. In proso millet, the race ovatum was found to have considerably higher grain nutrients than other races (Vetriventhan and Upadhyaya, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Earlier studies have reported protein content of 9.2 to 11.2% using a few germplasm (Kulkarni and Naik, 2000;Kewat et al, 2016). Average Zn (23-25 mg kg −1 ) and protein (7.9-8.5%) contents in the kodo millet accessions used in this study were greater than those in finger millet germplasm (Zn 19.9 mg kg −1 , protein 7.3%) (Upadhyaya et al, 2011a), and Ca content (190-213 mg kg −1 ) was greater than in foxtail millet (146 mg kg −1 ) (Upadhyaya et al, 2011b) and proso millet (165 mg kg −1 ) (Vetriventhan Table 7. In proso millet, the race ovatum was found to have considerably higher grain nutrients than other races (Vetriventhan and Upadhyaya, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…This accession was found resistant to three of the four isolates tested. In addition, ISe 1685 and ISe 1541 recorded higher grain yields compared with the best control, ISe 1468 (30). Therefore, these agronomically superior blast-resistant accessions can be directly released for cultivation in farmers' fields after thorough testing in yield trials in the relevant locations.…”
Section: Discussionmentioning
confidence: 99%
“…ISe 1419, which is resistant to sheath, neck, and head blast against all four isolates and has leaf blast resistance to two isolates (Fx 58 and Fx 60), was among the 26 best accessions with three or more agronomic and nutritional trait (Ca, Zn, and protein) combinations selected by Upadhyaya et al (30) from the foxtail millet core collection. Blastresistant accessions ISe 1059, -1181, and -1685, and ISe -1059 and -1187, were among the trait-specific accessions identified for Ca and Fe content, respectively (30). ISe 1067 and germplasm check ISe 1541 were identified as the best sources of protein among the 16 blast-resistant accessions.…”
Section: Discussionmentioning
confidence: 99%
“…For the past two decades, germplasm characterization at ICRISAT has led to the establishment of core and minicore collections for pearl millet (Bhattacharjee et al, 2007; Upadhyaya et al, 2009, 2011a), finger millet (Upadhyaya et al, 2006), and foxtail millet (Upadhyaya et al, 2008, 2011b) while only core collections was established for other small millets (Upadhyaya et al, 2014) ( Figure 1 ).…”
Section: Characterization Of Millet Germplasm For Grain Nutrientsmentioning
confidence: 99%